2020
DOI: 10.21037/atm.2019.12.132
|View full text |Cite
|
Sign up to set email alerts
|

A two-circular RNA signature of donor circFOXN2 and circNECTIN3 predicts early allograft dysfunction after liver transplantation

Abstract: Background: Early allograft dysfunction (EAD) following liver transplantation is associated with poor recipient and graft survival. In recent years, circular RNAs (circRNAs) have emerged as important components of endogenous RNAs. This study aims to explore the expression profile and predictive value of graft circular RNAs for EAD after liver transplantation.Methods: RNA sequencing was conducted to identify the circRNA profile in donor liver tissues. Furthermore, quantitative real-time polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Further research has revealed that PPARα is downregulated after LT, which might be an adaptive response to oxidative stress and hepatocellular damage during LT ( 16 ). Moreover, microRNAs and circular RNAs, such as miRNA-122, circFOXN2, and circNEXTIN3, that are expressed in the liver have been found to be potential early predictors of the onset of EAD ( 6 , 7 ). In addition, serum protein profiles of recipients associated with EAD have been widely studied, and several serum proteins have been identified, such as monocyte chemoattractant protein 1, interleukin 8, factor V, and soluble CD163 ( 8 , 9 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research has revealed that PPARα is downregulated after LT, which might be an adaptive response to oxidative stress and hepatocellular damage during LT ( 16 ). Moreover, microRNAs and circular RNAs, such as miRNA-122, circFOXN2, and circNEXTIN3, that are expressed in the liver have been found to be potential early predictors of the onset of EAD ( 6 , 7 ). In addition, serum protein profiles of recipients associated with EAD have been widely studied, and several serum proteins have been identified, such as monocyte chemoattractant protein 1, interleukin 8, factor V, and soluble CD163 ( 8 , 9 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors could contribute to the onset of EAD, such as donor age, donor body mass index (BMI), graft steatosis, cold ischemic time (CIT), warm ischemic time (WIT), donor serum sodium, and model for end-stage liver disease (MELD) score (5). Recently, multiple molecular markers of EAD have been introduced and improved the predicting profiles of EAD, such as microRNAs, circRNAs, and serum proteins (6)(7)(8)(9). However, the role of protein expression patterns in pretransplant liver grafts in predicting the onset of EAD and recipients' prognosis remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the contents and categories of current related studies are relatively similar, there are only a few examples, which are no longer explained in detail here. For instance, circHIPK3 was proven to modulate the proliferation of airway smooth muscle cells by the miR-326/STIM1 axis in asthma ( 69 ), a group of ample circRNAs and ceRNA networks were found to likely contribute to acquired immune deficiency syndrome (AIDS) ( 70 ), and a two-circular RNA signature of donors was thought to be a biomarker of early allograft dysfunction after liver transplantation ( 71 ). In addition to the above diseases, circRNAs play vital roles in a variety of immunological diseases and immune cells.…”
Section: Roles Of Circrnas In Immune-related Diseasesmentioning
confidence: 99%
“…1 However, apart from the organ shortage as the major limitation of LT, 2 early allograft dysfunction (EAD) following LT is considered a critical complication, with an incidence of approximately 20-40%, seriously affecting the long-term survival rate of allografts and recipients. [3][4][5][6][7] EAD is a multifactorial complication of LT, and its risk factors include the donor risk index, surgery-related factors, and Model for End-stage Liver Disease score. [7][8][9] Liver ischemia-reperfusion (IR) injury after surgery, a key factor for EAD development, is a complex process involving immune responses, inflammation, cell damage, and cell death, all of which are regulated by multiple cell lineages.…”
Section: Introductionmentioning
confidence: 99%